2018
DOI: 10.1037/xhp0000442
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of form- and meaning-based predictability on perceived clarity of speech.

Abstract: The perceptual clarity of speech is influenced by more than just the acoustic quality of the sound; it also depends on contextual support. For example, a degraded sentence is perceived to be clearer when the content of the speech signal is provided with matching text (i.e., form-based predictability) before hearing the degraded sentence. Here, we investigate whether sentence-level semantic coherence (i.e., meaning-based predictability), enhances perceptual clarity of degraded sentences, and if so, whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 32 publications
(68 reference statements)
6
45
2
Order By: Relevance
“…We tend to hear what we expect to hear-this is a common observation and recently supported by data showing that the perceived clarity of degraded speech is enhanced by both predictability based on form (i.e., phonological/lexical) at the word level and on meaning (i.e., semantic) at the sentence level (Signoret et al 2018). For individuals with hearing impairment (HI) who may struggle particularly hard to understand degraded speech, the potential support of such predictability could be invaluable.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…We tend to hear what we expect to hear-this is a common observation and recently supported by data showing that the perceived clarity of degraded speech is enhanced by both predictability based on form (i.e., phonological/lexical) at the word level and on meaning (i.e., semantic) at the sentence level (Signoret et al 2018). For individuals with hearing impairment (HI) who may struggle particularly hard to understand degraded speech, the potential support of such predictability could be invaluable.…”
Section: Introductionmentioning
confidence: 57%
“…For individuals without HI, this effect, known as the "pop-out effect," has been investigated extensively (Davis et al 2005;Davis & Johnsrude 2007;Hervais-Adelman et al 2011;Wild et al 2012), whereas it has not, to our knowledge, been reported whether individuals with HI experience the pop-out effect. For individuals without HI, presenting matching text only 200 msec before presenting a degraded spoken sentence, improves the perceived clarity of the sentence more than meaningless consonant strings (Wild et al 2012;Signoret et al 2018). This improvement in perceptual clarity is thought to be related to knowledge-based predictions about the phonological/lexical form of the upcoming word influencing upcoming speech processing (Sohoglu et al 2014;Signoret et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Auditory cortex is positioned in a hierarchy of speech processing regions that include both ascending and descending projections (Davis and Johnsrude, 2007;Peelle et al, 2010a) . Auditory cortex is sensitive not only to changes in acoustic information, but also reflects top-down effects of expectation and prediction (Sohoglu et al, 2012;Wild et al, 2012;Signoret et al, 2018) . Thus, the observed age differences in auditory cortex may reflect differential top-down modulation of auditory activity in young and older adult listeners.…”
Section: Discussionmentioning
confidence: 99%